ChemInform Abstract: Preparation of 4, 5‐Disubstituted‐2H‐1, 2, 3‐triazoles from (Z)‐2, 3‐Diaryl Substituted Acrylonitriles. Issue 52 (29th December 2014) - Madadi, Nikhil Reddy; Penthala, Narsimha Reddy; Song, Lin; Hendrickson, Howard P.; Crooks, Peter A.
Abstract A facile procedure for the synthesis of 4, 5‐diaryltriazoles (II) (15 examples) via cycloaddition of the title acrylonitriles with sodium azide ‐ a viable alternative to t he synthesis of triazoles via the Huisgen cycloaddition ‐ is given.